A Systematic Review of the Antimony Content of the Normal Human Prostate Gland - Zaichick, Vladimir (Journal of Hematology and Oncology Research, 2020)
The prostate gland is subject to various disorders. The etiology and pathogenesis of these diseases remain not well understood. Moreover, despite technological advancements, the differential diagnosis of prostate disorders has become progressively more complex and controversial. It was suggested that the antimony (Sb) level in prostatic tissue plays an important role in prostatic carcinogenesis and its measurement may be useful as a cancer biomarker. These suggestions promoted more detailed studies of the Sb content in the prostatic tissue of healthy subjects. The present study evaluated by systematic analysis the published data for Sb content analyzed in prostatic tissue of “normal” glands. This evaluation reviewed 1998 studies, all of which were published in the years from 1921 to 2020 and were located by searching the databases PubMed, Scopus, ELSEVIER-EMBASE, Cochrane Library, and the Web of Science. The articles were analyzed and “Median of Means” and “Range of Means” were used to examine heterogeneity of the measured Sb content in prostates of apparently healthy men. The objective analysis was performed on data from the 23 studies, which included 1173 subjects. It was found that the range of means of prostatic Sb content reported in the literature for “normal” gland varies widely from 0.0066 mg/kg to 0.071 mg/kg with median of means 0.0085 mg/kg on a wet mass basis. Because of small sample size and high data heterogeneity, we recommend other primary studies be performed.
Keywords: Antimony; Human prostate; Normal prostatic tissue; Biomarkers